Nutritional Composition, Heavy Metals And Antioxidative Properties Of Multigrain Beverage Powder - Rosly, Siti Munirah (University Science Malaysia, 2019)
The demand on healthier choice of food and beverages is increasing around the world due to a healthier lifestyle. Therefore, multigrain products are created. The multigrain consists of more than one grain types such as wheat, corn, sesame seed, rice, millet and other. This study is aimed to investigate the nutritional composition, heavy metals and antioxidative properties of multigrain beverage powder. The nutritional composition was determined by measuring the proximate content (moisture, fat, protein, ash, crude fibre and carbohydrates), dietary fibre (total, insoluble and soluble), heavy metals (Pb and Cd) and minerals (Ca, K, Fe, Zn, Cu, Mn and Mg). From the results, the nutritional composition of multigrain powder had higher carbohydrate (75.6 ± 0.30 %) and ash (3.8 ± 0.00 %) but lower in moisture (5.9 ± 0.40 %), fat (6.5 ± 0.70 %) and protein (8.2 ± 0.20 %) compared with other multigrain mix from previous study. The sample also had higher than single grain in term of total dietary fibre (17.5 ± 0.30 %) and trace elements (potassium: 778.7 ± 95.4 mg/100 g and magnesium: 111.2 ± 2.2 mg/100 g). The multigrain powder also had acceptable level of cadmium and zero amount of lead. The antioxidative properties of the sample were analysed by three different methods: DPPH, FRAP and ABTS. The result indicated that antioxidant in multigrain mix (FRAP: 12.3 mg Trolox/g dry weight & ABTS: 4.8 mg/Trolox/g dry weight) was higher than in single grain such as in rice bran and rice husk. The sample of this study had higher antioxidant (DPPH: 86.3 %) compared to the DPPH value with previous study (different multigrain mix).